Formation in Interprofessional Education in Nursing and Medical Students Globally. Scoping review - Macías Inzunza, Lylian; Rocco Montenegro, Víctor; Rojas Reyes, Jennifer; Baeza Contreras, Marcela; Arévalo Valenzuela, Carolina; Munilla González, Viviana (Investigación y Educación en Enfermería, 2020)
Objective. This work sought to know the state of the art related to the theme of Interprofessional Education (IPE) in the training of Nursing and Medical students and the level of evidence developed thus far. Methods. This was an exploratory systematic review, declared as scoping review by the Joanna Briggs Institute, JBI, in which a search was performed in Embase, Science direct, Pubmed-Medline, Academic search complete, BVS, Scopus and ERIC databases, limiting between 2009 - 2019 by using the DeCS and MeSH terms of Interprofessional education, education research, healthcare professionals, nursing and medicine, selecting 39 original articles after carrying out the review process with the criteria by the JBI. Results. Four thematic nuclei emerged: Experiences and perceptions of interprofessional learning, Didactics related with IPE, Empirical indicators related with IPE, and Development of professional skills. The highest level of evidence is presented by the articles dealing with didactics; on the contrary, no articles were found that dealt with topics related with early inclusion of IPE in the medical and nursing curricula, which are currently necessary to complement the focus of patient-centered care. Conclusion. The thematic nuclei show that the level of evidence in the literature is varied, although mostly descriptive in scope, highlighting the development of professional skills as a result of interprofessional education.